2017
DOI: 10.1021/acs.est.7b04177
|View full text |Cite
|
Sign up to set email alerts
|

Sulfidation of Iron-Based Materials: A Review of Processes and Implications for Water Treatment and Remediation

Abstract: Iron-based materials used in water treatment and groundwater remediation-especially micro- and nanosized zerovalent iron (nZVI)-can be more effective when modified with lower-valent forms of sulfur (i.e., "sulfidated"). Controlled sulfidation for this purpose (using sulfide, dithionite, etc.) is the main topic of this review, but insights are derived by comparison with related and comparatively well-characterized processes such as corrosion of iron in sulfidic waters and abiotic natural attenuation by iron sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
163
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 373 publications
(179 citation statements)
references
References 189 publications
(448 reference statements)
6
163
0
2
Order By: Relevance
“…[ 26,29 ] Second, the incorporated sulfur lowers electron transfer resistance from Fe 0 to the contaminant. [ 32,33 ] Third, the incorporated sulfur blocks adsorption sites for atomic hydrogen and inhibits the water reduction reaction and H 2 evolution. All are possible, but evidence for these proposed mechanisms is limited to a few observations, and the limited characterization of SNZVI makes differentiating between these mechanisms difficult.…”
Section: Figurementioning
confidence: 99%
“…[ 26,29 ] Second, the incorporated sulfur lowers electron transfer resistance from Fe 0 to the contaminant. [ 32,33 ] Third, the incorporated sulfur blocks adsorption sites for atomic hydrogen and inhibits the water reduction reaction and H 2 evolution. All are possible, but evidence for these proposed mechanisms is limited to a few observations, and the limited characterization of SNZVI makes differentiating between these mechanisms difficult.…”
Section: Figurementioning
confidence: 99%
“…Contaminants are transformed and removed by the same mechanisms [133,134]. An affordable bimetallic system that has been successfully tested is one entailing the addition of sulfur [123,135,136].…”
Section: The Nature Of the Conductive Metalmentioning
confidence: 99%
“…Orange I removal k obs rate of S-nZVI is 71.8 times higher than the one without sulfidation [21]. Many results showed that sulfidation conditions had great effects on target pollutants degradation efficiency [15,17,19,20]. For example, Cao et al found that the removal of antibiotic florfenicol was strongly dependent on S/Fe and the surface-areanormalized reaction rate constant of antibiotic florfenicol on S-nZVI at the optimal S/Fe molar ratio (0.14) was 48 times higher than nZVI [22].…”
Section: Introductionmentioning
confidence: 97%
“…Recently, many studies have revealed that surface sulfidation can control the corrosion and improve the conductivity of nZVI [15][16][17]. Because FeS has a higher electronegativity (5.02 V) than nZVI (4.04 V), the electrons generated from the corrosion process of nZVI can transfer to FeS.…”
Section: Introductionmentioning
confidence: 99%